Enzymatic in vitro antidiabetic of Cemumar (Micromelum pubescens), Tebengau (Ehretia laevis), and Kedondong (Spondias dulcis) leaves extract - Zarina, Zawawi (Universiti Malaysia Perlis, 2011)
Access is limited to UniMAP community.